Partial Intravenous Anaesthesia (PIVA) in a Neonate Maned Wolf (Chrysocyon Brachyurus) - Alves, Daniele Cristina; Lopes, Danielle Mara; Lucas, Nelson Dias; Carrera, Alefe Luiz Caliani; Tamamoto, Beatriz Kaori; Carneiro, Lilian Freire Lima; Debiage, Rafael Rostirolla; Fukushima, Fabíola Bono (Acta Scientiae Veterinariae, 2023)
Background: The maned wolf (Chrysocyon brachyurus) is the largest canid in South America and the only representative of its genus. The scientific literature presents studies referring to the management and anaesthesia of the species but is scarce in case of emergency procedures, and to date, there are no reports of anaesthesia for emergency procedures in a neonatal maned wolf. Thus, this study aimed to report xenotransfusion and emergency anaesthesia for thoracic limb amputation in an approximately 8-days-old maned wolf pup. Case: A maned wolf pup, approximately 8-days-old, with a history of an accident with an agricultural machine, was referred to the Veterinary Hospital of the Federal University of Paraná - Palotina Sector (HVP - UFPR) with a grade III open fracture of left radius and ulna. At the physical evaluation, bullous rales were observed in the right caudal lobe on pulmonary auscultation, hypoglycemia and severe dehydration, the latter being determined by the occurrence of enophthalmos, increased capillary refill time and skin turgor (3 s). The hemogram revealed regenerative hypochromic macrocytic anaemia, thrombocytopenia and leukopenia, and the chest radiograph showed alveolar pattern opacification, associated with the presence of air bronchograms in the caudal lobes, more evident on the right side, suggestive of pulmonary contusion. Considering the laboratory alterations and the need for amputation of the thoracic limb, xenotransfusion was chosen before the anaesthetic procedure. The animal was pre-medicated with methadone 0.2 mg/kg and anaesthetic induction was performed with propofol titrated to effect, requiring 10 mg/kg. This was followed by endotracheal intubation and anaesthetic maintenance using the partial intravenous technique with an infusion of 5 µg/kg/h of remifentanil and Isoflurane vaporised through a non-rebreathing system in oxygen at 0.6. Anaesthetic monitoring included heart rate and electrocardiogram tracing, respiratory rate, oxyhemoglobin saturation, end-tidal partial pressure of carbon dioxide, systemic blood pressure by the oscillometric method, and oesophageal body temperature. Although the blood tests after the transfusion showed an increase in hematocrit, changes suggestive of a delayed hemolytic reaction because of the transfusion were also noticed. Discussion: Preanesthetic stabilisation is critical, as anaesthesia of unstable patients may result in a higher risk of anaesthetic complications. Critically ill patients may present systemic imbalances that can trigger pharmacokinetic and pharmacodynamic changes of anaesthetics and analgesics. Neonates have several marked physiological differences, since some organs are still immature, have a high body volume of water, and present a reduced amount of total fat and concentrations of circulating proteins, making it necessary to adjust protocols and doses used for these patients. Blood transfusion between the same species is always the best option, though xenotransfusion becomes an option when there is no homologous donor available. However, it can present a great risk to life, as there is a lack of studies regarding the blood typing of the species and blood compatibility tests. We concluded that there was an increase in hematocrit after 24 h of xenotransfusion and, even with signs of delayed hemolytic reaction observed in the blood test, the patient did not show specific clinical signs of transfusion reaction. The pup was sensitive to methadone but required a high dose of propofol for anaesthetic induction. The use of methadone as a pre-anaesthetic agent and the infusion of remifentanil provided adequate analgesia based on the parameters evaluated. Keywords: xenotransfusion, stabilisation, anaesthesia, neonatal. Título: Anestesia intravenosa parcial (AIVP) em uma lobo-guará (Chrysocyon brachyurus) neonata Descritores: xenotransfusão, estabilização, anestesia, neonato.